"The best period of my life": The academy as a Safe Haven for Israeli trans students. Issue 3 (2nd April 2020) - Tsfati, Maya; Nadan, Yochay
ABSTRACT: This article examines the experiences of Israeli trans students, revealing the meanings they ascribe to their social interactions in the academic environment and outside it. Based on an analysis of 20 semi-structured interviews with Israeli trans students studying in several academic institutions, we show that their experiences reflect their movement between two realms: one of risk and one of safety. These realms are inter-related because each helps to define the other. The participants' experiences of victimization in various non-academic social arenas endow the academy with comforting meanings that foster feelings of safety among participants and contribute to their self-agency.